Pengaruh Pemberian Kompos Pasar terhadap Pembibitan Bibit Kakao (Theobroma cacao L.) - Elviani, Yolla Daranti; Situmorang, Helentina; Fajri, Fajri (Mahesa Research Institute, 2026)
This study aimed to determine the effect of market waste compost on the growth of cocoa (Theobroma cacao L.) seedlings and to determine the most effective dose in improving growth parameters. The study was conducted from March to July 2025 in Padang Rajo, Harau District, Lima Puluh Kota Regency, West Sumatra. The design used was a Completely Randomized Design (CRD) with five market waste compost dosage treatments (0 g, 200 g, 300 g, 400 g, and 500 g per polybag) and five replications. The parameters observed included plant height, number of leaves, leaf width, leaf length, and stem diameter. The results showed that the application of market waste compost significantly affected seedling height, number of leaves, leaf length, and leaf width. A dose of 200 g produced the highest seedling height and leaf width, while a dose of 300 g produced the highest number and length of leaves. However, compost application did not significantly affect stem diameter. Too high a compost dosage actually tends to reduce growth effectiveness, possibly due to an imbalance of nutrients in the planting medium. Thus, the use of market waste compost in growing media has been proven effective in increasing the vegetative growth of cocoa seedlings when administered in the correct dosage.